Isowighteone attenuates vascular calcification by targeting HSP90AA1-mediated PI3K-Akt pathway and suppressing osteogenic gene expression - Mo, Yuanxi; Jin, An; Hong, Wanzi; Peng, Jiahui; Yang, Rui; Song, Qiqi; Liu, Yaoxin; Cheng, Yuqi; Wong, Wing-Tak; Huang, Qian; Jiang, Lei; Xu, Zhaoyan; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundIsowighteone, an isoflavonoid compound derived from Ficus hispida L.f. (F. hispida, Moraceae), has demonstrated significant anti-inflammatory properties in prior studies. However, its anti-inflammatory role in vascular calcification is unclear.ObjectWe investigated the efficacy of isowighteone in the treatment of vascular calcification, explored its potential mechanism, and determined whether isowighteone is a safe and effective treatment.MethodsIn this study, we isolated three natural compounds and evaluated their efficacy using in vitro calcification models through CCK-8 assays, Alizarin Red staining, and calcium quantification. The key targets of Isowighteone were identified via network pharmacology and molecular docking analyses. The anti-calcification effect of Isowighteone was further assessed in a mouse model of vascular calcification. Alizarin Red staining, calcium quantification, and immunofluorescence were employed to evaluate its therapeutic potential. Additionally, quantitative real-time PCR (qRT-PCR) and Western blot were used to examine the mRNA and protein expression levels of osteogenic markers. The impact of Isowighteone on the HSP90AA1/PI3K/Akt signaling pathway in vascular calcification was also investigated using Western blot analysis.ResultsAlizarin red staining and Calcium quantification experiments demonstrated that Isowighteone reduces aortic vascular calcification in mice and decreases calcification levels in Human aortic smooth muscle cells (HASMCs). Network pharmacology and molecular docking analysis reveals the HSP90AA1 protein as the specific target of isowighteone in HASMCs which PI3K-Akt is pivotal regulatory signaling pathway in this mechanism. Additionally, this study proved Isowighteone downregulated osteogenic gene expression in HASMCs, thereby inhibiting cellular calcification and preventing the process of VC by in vivo study, as evidenced by qRT-PCR and Western blot.ConclusionIsowighteone demonstrates significant therapeutic potential by effectively downregulating the expression of osteogenic genes, alleviating vascular calcification, and suppressing the HSP90AA1/PI3K/Akt signaling pathway, thereby improving pathological conditions associated with vascular calcification. These above results not only elucidate isowighteone as a novel therapeutic agent against VC through selective suppression of osteogenic differentiation but also position this phytochemical as a clinically candidate for VC management.